Making land available for affordable housing: challenges for local government - Thellane, Malimakatso Louisa (My University, 2009)
Abstract This research report addresses the challenges facing local government in making land available for affordable housing. It seeks to establish what challenges the three leading South African metropolitan municipalities of Johannesburg, Cape Town and eThekwini face in their attempts at making land available for affordable housing. Affordable housing is defined in this research as the housing market segment for households earning between R3500 and R10,000 per month, which is usually referred to as ‘the gap market’ and which represents housing opportunities in the price range between R100,000 and R400,000. Many studies have argued that a combination of historical and policy options that have evolved in the post apartheid South Africa has caused this sector of the housing market to be conspicuously under-catered for by the private housing sector and as a result of Government’s focus on low income ‘RDP’ housing. This research, specifically focuses on obstacles to land availability. The research is exploratory in intent and qualitative in its approach. It relies on desktop research, supplemented by in-depth interviews of 16 strategically placed government and private sector representatives of the housing sector. The research reviews literature which touches on the concepts and debates relating to the complexity of accessing urban land for housing, from both international and local perspectives. Access to land for housing is a complex web of interacting factors, with intense debates surrounding the need for regulation or not. Affordable housing in a competitive urban environment fails due to its weak financial basis. The research arrives at the conclusion that the land question is particularly complex in South Africa arising from its clear but cumbersome policy and legislative framework. From a political and institutional perspective the research points out that there is the need to understand the political processes that impact on land and housing. Another finding is that there is obstructive use of legislation and, together with a reluctance to implement policy, significantly contribute to curtailing access to land for affordable housing The research concludes that the impediments result from a mixture of factors that include (i) the availability of land, (ii) the political, policy and legislative processes involved in its acquisition, (iii) the nominal and mandated roles of the metropolitan authorities and the private sector, (iv) the interplay between the regulated and non-regulated markets, (v) local human resource capabilities and administrative matters across the spheres of government, in particular within the municipalities for dealing with cumbersome administrative steps and processes which require many people to deal with land transactions, and (vi) the obstructive use of legislation. Finally the observation is made that there is the need for a concerted effort to understand, confront and remedy these complex interacting factors to enable affordable housing to find its place in the housing spectrum.